Penerapan Kebijakan Sistem Pembelajaran Berbasis Digitalisasi Di SMK Islam Tikung Lamongan - Syafi'i, Imam (CV ODIS, 2024)
This study aims to examine and analyze the implementation of digital-based learning system policies at SMK Islam Tikung Lamongan. Data collection was conducted through questionnaires and interviews with the principal of SMK Islam Tikung Lamongan, the vice principal, and computer science teachers. The results show that the implementation of digital-based learning system policies has a positive impact on the development of the school, particularly at SMK Islam Tikung Lamongan.